PELAKSANAAN PEMBELAJARAN JARAK JAUH (PJJ) DI TENGAH PANDEMI COVID- 19 PADA MATA PELAJARAN BIOLOGI KELAS X SMA NEGERI 2 MEDAN TP. 2020/2021 - Simbolon, Jimmy Francius (Jurnal Ilmiah Aquinas, 2021)
This research is a descriptive study which aims to obtain an overview of the implementation of distance learning (PJJ) in the middle of the Covid-19 pandemic in biology subject in Class X SMA Negeri 2 Medan TP. 2020/2021. The research subjects were students of class X. The research instruments were interviews with the teacher and giving questionnaires to students. The results showed that: Teachers and students of Class X SMA Negeri 2 Medan TP. 2020/2021 has implemented Distance Learning (PJJ). Students carry out PJJ every day, an average of 5-6 hours per day. Students take online classes provided by the teacher, namely Google Classroom, interact via video conference (zoom cloud meeting), Instagram, group chat (telegram, whatsapp), as well as through other online learning applications. Students think they can still understand the learning material, it's fun, it's easy to get learning resources, and can still concentrate. However, some students complained that they could not ask directly to the teacher or friends, and were bored. .